Matriz intelectual y espiritual contestataria: el contexto del modernismo rubendariano - Subercaseaux, Bernardo (Nueva Revista del Pacífico, 2016)
Resumen: Nos proponemos perfilar la matriz intelectual y espiritual de fines del siglo XIX, matriz contestataria respecto a la modernidad finisecular, que está presente con rasgos diferentes en Europa, España e Hispanoamérica, dependiendo del contexto socio-histórico de cada zona. Matriz que permite vislumbrar en Darío una crítica al entusiasmo con la modernidad del positivismo burgués finisecular. Planteamos que esta matriz debe tenerse en cuenta en la lectura de su obra desde Azul (1888), lo que argumentamos en relación a esta perspectiva relevamos el contexto intelectual y literario presente en la génesis de su poesía como una variable a considerar en la lectura de la misma.Palabras claves: modernismo, siglo XX, Ruben Darío, poesía.Abstract: This article intends to draw the intellectual and spiritual matrix that arises as a response to modernity at the end of the 19th century, and which expresses differently in Europe, Spain and Hispanic America, depending on the social and historical contexts in each region. In Darío, this matrix evinces a criticism against the enthusiasm towards the modernity of bourgeois positivism at the end of the 19th century. We propose that this matrix should be considered in the reading of Darío’s work since Azul (1888), and in this case, in the sonnet “De invierno”, populated by luxurious objects related to the oligarch imaginary. In this light we think it relevant to consider the intellectual and literary contexts present in the genesis of his poetry as factors for its reading and interpretation.Keywords: modernity, 19th century, Ruben Darío, poetry.